Iron-based trinuclear metal-organic nanostructures on a surface with local charge accumulation - Krull, Cornelius; Castelli, Marina; Hapala, Prokop; Kumar, Dhaneesh; Tadich, Anton; Capsoni, Martina; Edmonds, Mark T; Hellerstedt, Jack; Burke, Sarah A; Jelinek, Pavel; Schiffrin, Agustin (Nature communications, 2018)
Coordination chemistry relies on harnessing active metal sites within organic matrices. Polynuclear complexes-where organic ligands bind to several metal atoms-are relevant due to their electronic/magnetic properties and potential for functional reactivity pathways. However, their synthesis remains challenging; few geometries and configurations have been achieved. Here, we synthesise-via supramolecular chemistry on a noble metal surface-one-dimensional metal-organic nanostructures composed of terpyridine (tpy)-based molecules coordinated with well-defined polynuclear iron clusters. Combining low-temperature scanning probe microscopy and density functional theory, we demonstrate that the coordination motif consists of coplanar tpy's linked via a quasi-linear tri-iron node in a mixed (positive-)valence metal-metal bond configuration. This unusual linkage is stabilised by local accumulation of electrons between cations, ligand and surface. The latter, enabled by bottom-up on-surface synthesis, yields an electronic structure that hints at a chemically active polynuclear metal centre, paving the way for nanomaterials with novel catalytic/magnetic functionalities.